PENGARUH PEMBELAJARAN MICRO TEACHING DAN PROGRAM PENGALAMAN LAPANGAN (PPL) TERHADAP MINAT MENJADI GURU PADA MAHASISWA - Novita Sari; Trisno Martono; Sri Wahyuni (Department of Economics Education, Universitas Sebelas Maret, 2017)
This research is aimed to identify (1) the influence of Micro Teaching learning and Field Experience Program (PPL) towards the interest of becoming a teacher of the Economic Education students in the year of 2017; (2) the influence of Micro Teaching learning towards the interest of becoming a teacher of the Economic Education students in the year of 2017; (3) the influence of Field Experience Program (PPL) towards the interest of becoming a teacher of the Economic Education students in the year of 2017.This research includes as a qualitative research. The research includes as a population research. The data was collected by distributing questionnaires. The validity of the data was obtained through the result of tryout of 30 respondents. The data were analyzed by using multiple linear regression analysis. The research finding shows that: (1) the value of F-test is obtained Fcount>Ftable (5,736>3,14) with the value of p = 0,005, therefore Ho is rejected and Ha is accepted. It means that there is a significant influence between Micro Teaching learning and Field Experience Program (PPL) simultaneosly towards the interest of becoming a teacher. (2) the value of t-test with the variable of Micro Teaching learning is tcount>ttable (2,009>1,99) with the value of p = 0,049, therefore Ho is rejected and Ha is accepted. It means that there is a significant influence between Micro Teaching learning and Field Experience Program (PPL) partially towards the interest of becoming a teacher. (3) the value of t-test with the variable of Field Experience Program (PPL) is tcount>ttable (2,157>1,99) with the value of p = 0,035, therefore Ho is rejected and Ha is accepted. It means that there is a significant influence of the variable of Field Experience Program (PPL) partially towards the interest of becoming a teacher. (4) the determinant coeffisient (Adjusted R Square) is 0,127. It can be concluded that 12,7% of interest of becoming a teacher is influenced by Micro Teaching learning and Field Experience Program (PPL), meanwhile the rest of 87,3% is influenced by various factors which are not included in this research.